Masshtaby sorevnovatel'noi deyatel'nosti bortsa - Chumakov, E. M. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to substantiate the new approach to the analysis of a wrestler`s competitive activities. The author offers to consider a wrestler`s competitive activities in a scale. It were selected some levels in connection with it: the performing of elementary actions; the activities of a wrestler when fighting; the activities of a wrestler in parts of the competitions; the activity of the wrestler in the whole competition; the activity of a wrestler in the totality of competitions. Aims, time, place, evaluation, the main and the auxiliary orientation of the activities and the means of control are determined for every mentioned level.